CHAPTER 6.4 THE OLDEST ROCK ASSEMBLAGES OF THE SIBERIAN CRATON - Rosen O.M.; Turkina O.M. (My University, 2007)
This chapter elaborates the oldest rock assemblages of the Siberian Craton. The Siberian Craton that occupies an area of approximately 4 × 10 6 km2 is overlain largely by Mesoproterozoic to Phanerozoic sedimentary rocks, whose thickness ranges between 1 and 8 km, averaging approximately 4 km. The Siberian Craton consists of large geologic elements, including component, primordial microcontinents that accreted at ∼2.6 and 1.8 Ga to form a single craton. The Sharyzhalgay basement uplift is the southernmost exposed part of the Tungus province of the Siberian Craton. This uplift extends for 350 km from the Oka River in the west to the southern part of Lake Baikal. The Irkut and Kitoy domains are dominated by Archean high-grade gneisses, mafic and felsic granulites, and amphibolites. Their protoliths are basalt, andesite, and dacite volcanic rocks. The Magan terrane consists mainly of orthopyroxene-plagioclase gneisses, enderbites, and charnockites, with rare two-pyroxene metamafic rocks, all of which are named as a whole as the Upper Anabar Group.